Synthesis of three different galactose-based methacrylate monomers for the production of sugar-based polymers. (2nd September 2016) - Desport, Jessica S.; Mantione, Daniele; Moreno, Mónica; Sardón, Haritz; Barandiaran, María J.; Mecerreyes, David
Abstract: Glycopolymers, synthetic sugar-containing macromolecules, are attracting ever-increasing interest from the chemistry community. Glycidyl methacrylate (GMA) is an important building block for the synthesis of sugar based methacrylate monomers and polymers. Normally, glycidyl methacrylate shows some advantages such as reactivity against nucleophiles or milder synthetic conditions such as other reactive methacrylate monomers. However, condensation reactions of glycidyl methacrylate with for instance protected galactose monomer leads to a mixture of two products due to a strong competition between the two possible pathways: epoxide ring opening or transesterification. In this paper, we propose two alternative routes to synthesize regiospecific galactose-based methacrylate monomers using the epoxy-ring opening reaction. In the first alternative route, the protected galactose is first oxidized to the acid in order to make it more reactive against the epoxide of GMA. In the second route, the protected sugar was first treated with epichlorohydrin followed by the epoxy ring opening reaction with methacrylic acid, to create an identical analogue of the ring-opening product of GMA. These two monomers were polymerized using conventional radical polymerization and were compared to the previously known galactose-methacrylate one. The new polymers show similar thermal stability but lower glass transition temperature (Tg) with respect to the known galactose methacrylate polymer. Graphical abstract: Highlights: Synthesis of three different methacrylate monomers based on galactopyranose. Glycidyl methacrylate (GMA) ring opening mechanisms is investigated. Regiospecific syntheses are described. Two new sugar-based polymers synthesize using free-radical polymerization. Characterization of the new polymers with TGA, DSC and GPC.